Optimizing livestock carrying capacity for wild ungulate-livestock coexistence in a Qinghai-Tibet Plateau grassland - Yueheng Ren (Nature Portfolio, 2021)
Abstract Wild ungulates are an important part of terrestrial ecosystems and play a critical role in maintaining ecosystem health and integrity. In many grassland ecosystems that are habituated by wild ungulates, the coexistence of domestic ungulates has created a conflict over grazing resources. Solving this conflict requires a balanced and sustainable policy that satisfies both the needs of wildlife protection and food production. Here, we assess the optimal grassland livestock carrying capacity of an alpine grassland on the Qinghai-Tibet Plateau, given the coexistence of wild populations of kiangs (Equus kiang) and Tibetan gazelles (Procapra picticaudata), two key species grazing in this region. We use kriging and the MaxEnt method to estimate the population sizes of kiangs and Tibetan gazelles in Maduo County, Qinghai Province. We then convert the estimated population size of the two species into sheep units and calculate the residual carrying capacity for livestock grazing. We show that after accounting for the grazing need for kiangs and Tibetan gazelles, grassland in Maduo is capable of supporting 420,641 sheep units, which is slightly more than the current livestock population. However, the residual carrying capacity is highly uneven across the region, and overgrazing is found in many areas of Maduo, especially in northern Maduo. This research provides a useful framework for planning sustainable livestock farming for the Qinghai-Tibet Plateau and other regions facing wildlife-livestock conflict.